Wheat-related disorders: A broad spectrum of 'evolving' diseases. Issue 4 (August 2014) - Gasbarrini, GB; Mangiola, F
Throughout the world, cereals have always been recognized as a fundamental food. Human evolution, through the development of cooking, led to the production of food rich in gluten, in order to take full advantage of the nutritional properties of this food. The result has been that gluten intolerance has arisen only in those populations that developed the art of cooking wheat. It is also recognized that wheat, one of the central elements of the Mediterranean diet, cannot be tolerated in some individuals. Among the wheat-related pathologies, coeliac disease is the best known: it is a chronic inflammatory condition affecting the gastrointestinal tract, which develops in genetically predisposed individuals. The most common manifestation is the malabsorption of nutrients. Recently, another wheat-related disease has appeared: non-coeliac gluten sensitivity, defined as the onset of a variety of manifestations related to wheat, rye and barley ingestion, in patients in whom coeliac disease and wheat allergy have been excluded. In this paper we will explore the damaging power of wheat, analysing the harmful process by which it realizes the onset of clinical manifestations associated with wheat-related disorders.